Public discourses on choice of termination of pregnancy in a rural area of the Eastern Cape Province in South Africa - Sigcau, Nomakhosi (Rhodes University, Faculty of Humanities, Department of Psychology, 2009)
A period of ten years has elapsed since the Choice on Termination of Pregnancy Act came into effect. Little has been done in South Africa to investigate public discourses concerning termination of pregnancy since the implementation of the Act. The social context and the quality of available support systems determine the outcome of the women's feelings after the abortion. Knowledge about the social context is important, as it will help to understand the complexities and nuances of abortion. The aim of the research is to explore public discourses on Choice on Termination of Pregnancy (CTOP), and the potential implications of these discourses on the use of the CTOP service. The sample consisted of 23 black isiXhosa-speaking participants from the rural area of the Eastern Cape Province in South Africa. Four focus groups coming from different age groups (between the ages 18 and 52) with both men and women participated in the study. Fictitious vignettes that tap into two different scenarios regarding abortion based on women's stories were used. Discourses that emerged from people's text are explained, described and interpreted through a discourse analysis. Since the study was interested in public discourses it led to the discovery of 17 interpretative repertoires as follows: social stigma, abortion equated to murder, degradation of society, pregnancy as an irresponsible act, conditional acceptance, TOP in the context of marriage, future potentiality invested in the foetus, dehumanizing foetus into a clot, shared decision making responsibility, gender dynamics interpretative repertoire, negative post abortion consequences, the scolding versus the supportive nurse interpretative repertoire, alternatives interpretative repertoire, rights versus no responsibility interpretative repertoire, more knowledge needed, male and female or generational differentiation repertoire, and the positive effects repertoire. Abortion is opposed on religious and cultural grounds. TOP has been legalized in South Africa but with this a debate and conflicting views have arisen. These variations in people's discourses may limit access to TOP for women who need the service.
Keywords: Abortion -- South Africa -- Eastern Cape; Abortion -- Public opinion; Abortion -- Moral and ethical aspects; Abortion -- Social aspects; Abortion -- Psychological aspects; Discourse analysis -- South Africa